Soil pipe flow tracer experiments: 1. Connectivity and transport characteristics. Issue 8 (21st November 2015) - Wilson, G. V.; Rigby, J. R.; Ursic, M.; Dabney, S. M.
Abstract: Much debate has occurred in catchment hydrology regarding the connectivity of flow paths from upslope areas to catchment outlets. This study was conducted in two catchments, one with three upper branches, in a loess soil with a fragipan that fosters lateral flow and exhibits an extensive distribution of soil pipe collapse features. The study aimed to determine the connectivity of multiple soil pipe networks as well as determine pipe flow velocities during storm events. Fluorescein dye was injected directly into soil pipes at the upper most pipe collapse feature of four different hillslopes. Breakthrough curves (BTC) were determined by sampling multiple pipe collapse features downslope. The BTCs were used to determine the 'average' (centre of mass) and 'maximum' (first arrival) flow velocities. This study confirmed that these catchments contain individual continuous soil pipe networks that extend over 190 m and connect the upper most hillslopes areas with the catchment outlet. While the flow paths are continuous, the individual pipe networks consist of alternating reaches of subsurface flow through soil pipes and reaches of surface flow through gullies formed by pipe collapses. In addition, flow can be occurring both through the subsurface soil pipes simultaneous with surface flow generated by artesian flow from the soil pipes. The pipe flow velocities were as high as 0.3 m/s, which was in the range of streamflow velocities. These pipe flow velocities were also in the range of velocities observed in pinhole erosion tests suggesting that these large, mature soil pipes are still actively eroding. Copyright © 2015 John Wiley & Sons, Ltd.